Qualifying Differently: Reflecting on an Alternative Approach to Doctoral Comprehensive Exams - Kipp, Amy; Hawkins, Roberta (ACME, 2025)
In this paper, we build on critical scholarship calling for a care revolution in geography by examining the comprehensive/qualifying exam (QE) process as a moment of intervention. In North America, aspiring doctoral candidates are typically expected to pass a QE before beginning their research. The way QEs are traditionally designed and implemented in the field of geography reinforces a particular canon and a certain way of being a geographer that excludes diverse knowledges. Doctoral students often experience preparing for and completing these exams as a specifically stressful and isolating period. Such an approach to QEs limits geography’s potential as a caring discipline. From our positions as a doctoral student and PhD supervisor, we use collaborative autoethnography to explore an alternative QE format. To better understand the potential of alternative QEs to support doctoral education in geography, we bring literature on QEs into conversation with feminist geography literature on care and academia, exploring the educational possibilities of practicing QEs in a way aligned with a caring academic praxis. Rather than being viewed as a rigorous and individualized test focused on creating ‘expert geographers,’ we suggest the discipline thinks about QEs as a process that encourages scholars to practically and relationally engage with diverse ways of knowing. Despite its potential, doing QEs differently within an uncaring university system can be challenging. It requires a great deal of relational care work to be done well. In conclusion, we consider how geographers might begin to practice QEs differently in order to imagine the discipline, and academia, otherwise.